OPTIMASI SUHU PENGERINGAN DENGAN MENGGUNAKAN OVEN TERHADAP MUTU LADA HITAM DAN LADA PUTIH BUBUK - RTM Sutamihardja; Nia Yuliani; Oktavio Rosani (Universitas Nusa Bangsa, 2018)
Optimization of Drying Temperature Using Oven on Quality of Black Pepper and White Pepper Powder Pepper (Piper Nigrum L) is an Indonesian spice plant widely used for export and import activity. The post-harvest process of pepper affected the quality, especially on the drying process. One of secondary metabolite compound is piperin. Piperin is an active substance of alkaloid group giving a distinctive spicy flavor to the pepper. Drying process by using the oven could improve the quality of pepper. The results showed that the optimum temperature for white pepper was 85° C for 20 minutes with the water content of 10.65%, total mold/yeast was 1 x 104 colony/g, and piperin content of 4.58%. For Black pepper, the optimum temperature was at 105° C for 20 minutes with the moisture content of 7.84%, total mold/yeast was 1.3 x 104 colony/g and piperin 5,01%.Keywords: White Pepper, Black Pepper, Piperin Content.ABSTRAK Lada (Piper Nigrum L) adalah tanaman rempah Indonesia yang banyak digunakan untuk ekspor dan impor. Proses pasca panen lada yang tidak maksimal menyebabkan kualitas menurun. Lada memiliki senyawa metabolit sekunder berupa piperin. Piperin adalah zat aktif golongan alkoloid yang memberikan cita rasa pedas khas pada lada. Pengeringan dengan menggunakan oven mampu meningkatkan mutu lada. Hasil penelitian menunjukan suhu optimum untuk pengovenan lada putih adalah 85°C selama 20 menit dengan kadar air sebesar 10,65 %, AKK 1 x 104 koloni/ g, dan kadar piperin 4,58 %. Lada hitam efektif pada suhu optimum 105°C selama 20 menit dengan kadar air sebesar 7,84 %, AKK 1,3 x 104 koloni / g dan kadar piperin 5,01 %.Kata kunci : Lada Putih, Lada Hitam, Kadar Piperin